Acceleration of ions by electric field pulses in the inner magnetosphere. Issue 6 (12th June 2015) - Artemyev, A. V.; Liu, J.; Angelopoulos, V.; Runov, A.
Abstract Intense (∼5–15 mV/m), short‐lived (≤1 min) electric field pulses have been observed to accompany earthward propagating, dipolarizing flux bundles (flux tubes with a strong magnetic field) before they are stopped by the strong dipole field. Using Time History of Events and Macroscale Interactions during Substorms observations and test particle modeling, we investigate particle acceleration around L shell ∼7–9 in the nightside magnetosphere and demonstrate that such pulses can effectively accelerate ions with tens of keV initial energy to hundreds of keV. This acceleration occurs because the ion gyroradius is comparable to the spatial scale of the localized electric field pulse at the leading edge of the flux bundle before it stops. The proposed acceleration mechanism can reproduce observed spectra of high‐energy ions. We conclude that the electric field associated with dipolarizing flux bundles prior to their stoppage in the inner magnetosphere provides a natural site for intense local ion acceleration.